Pengaruh Likuiditas, Leverage, dan Perputaran Aset Terhadap Kinerja Masa Depan - Gusmiarni; Purwanti (LPPM STIE PPI, 2023)
Introduction/Main Objectives: To examine the effect of liquidity, leverage and asset turnover on the company's future performance both partially and simultaneously. Background Problem: To see whether the company can manage its current assets well to obtain profits and performance in the future. Novelty: This research re-examines previous research using secondary data in the form of financial report data for property and real estate sub-sector companies listed on the Indonesia Stock Exchange from 2018 to 2021. Research Method: Samples were taken from 20 companies using the proportional sampling method using using SPSS 24. Findings/Results: Partially liquidity has a negative and significant effect on future performance, leverage has a negative and significant effect on future performance, then asset turnover has a positive and significant effect on future performance. Meanwhile, simultaneously liquidity, leverage and asset turnover have a significant effect on future performance. Conclusion: Based on these results, all variables can be used as consideration in making decisions in order to improve the company's future performance.